Systematic characterization of the barrier function of diverse ex vivo models of damaged human skin - Barthe, Manon; Clerbaux, Laure-Alix; Thénot, Jean-Paul; Braud, Véronique M.; Osman-Ponchet, Hanan (Frontiers in Medicine, 2024)
Background The skin barrier plays a crucial role in protecting our body against external agents. Disruption of this barrier’s function leads to increased susceptibility to infections and dermatological diseases. Damaged skin can be due to the use of detergents, sunburn or excessive scratching. In the context of the COVID-19 pandemic the recommended hygiene measures to prevent the spread of SARS-CoV-2, such as wearing masks, frequent handwashing, and the use of sanitizers, can also potentially alter the skin barrier. Objectives The purpose of the study was to characterize the barrier function of ex vivo models of damaged human skin. Methods Skin barrier damage was induced through different chemical and mechanical treatments, representative of the potential factors damaging human skin. The skin barrier function was evaluated in terms of permeability, dermal absorption capacity, stratum corneum thickness and gene expression of barrier markers. As inflammation is linked to skin barrier integrity, inflammatory markers were also analyzed. Results and discussion The different treatments applied to ex vivo skin models allow the simulation of diverse degrees of skin damage, making these models valuable for assessing the efficacy of topical products targeted at skin repair and for studying the effects of compromised skin barrier on viral penetration.